Bone-seeking therapeutic radiopharmaceuticals - Srivastava Suresh C. (Brazilian Archives of Biology and Technology, 2002)
Bone-seeking therapeutic radiopharmaceuticals are utilized on the basis of the radionuclide?s particulate emissions (primarily low to intermediate beta emission). The requirements therefore are different from those of bone imaging agents that consist mainly of short-lived single photon emitters. Lately, the therapeutic bone seeking radiopharmaceuticals have attained increasing importance due to their potential role in alleviating pain from osseous metastases in cancer patients, for the treatment of joint pain resulting from inflamed synovium (radiosynoviorthesis, or radiosynovectomy), or from various other forms of arthritic disease. There is, however, a paucity of published data on the bio-pharmacokinetics of these agents when used following intravenous administration for bone pain palliation. This paper will briefly review and summarize the presently available chemical and biopharmacokinetic information on the various clinically approved as well as experimental bone-localizing therapeutic radiopharmaceuticals, and make projections on their clinical application for the treatment of primary/metastatic cancer in bone.